Notes on the genus Anomala Samouelle, 1819 (Coleoptera, Scarabaeidae, Rutelinae) in Vietnam and neighboring regions: eight new species and faunistic records - Zorn, Carsten; Kobayashi, Hirokazu; Wada, Kaoru (Contributions to Entomology = Beiträge zur Entomologie, 2017)
Eight new species of the genus Anomala Samouelle, 1819 are described from Vietnam: Anomala okushimai spec. nov., Anomala immeliorata spec. nov., Anomala confrater spec. nov., Anomala imperspicabilis spec. nov., Anomala ordinate spec. nov., Anomala recordata spec. nov., Anomala asaitoae spec. nov., and Anomala herbacea spec. nov. In addition, new and interesting records of Anomala species from Vietnam and neighboring regions are presented.Nomenclatural ActsAnomala okushimai spec. nov. – urn:lsid:zoobank.org:act:DB65AF09-2AD7-4B48-A64B-0D74C2A8C830Anomala immeliorata spec. nov. – urn:lsid:zoobank.org:act:94F6E08A-609F-45BD-90DC-C2357A94B080Anomala confrater spec. nov. – urn:lsid:zoobank.org:act:CF9C33FF-3E48-4583-B307-61BAC7F3D04AAnomala imperspicabilis spec. nov. – urn:lsid:zoobank.org:act:8B865ECA-A674-4C60-A04A-10B0B4196C34Anomala ordinata spec. nov. – urn:lsid:zoobank.org:act:1177FA2D-BF2B-417C-8B01-BD230DBC23DEAnomala recordata spec. nov. – urn:lsid:zoobank.org:act:53189F43-2F86-4D8B-B41D-9E5E4BD47013Anomala asaitoae spec. nov. – urn:lsid:zoobank.org:act:829A3E69-938F-4F9C-998A-C4FE117C5740Anomala herbacea spec. nov. – urn:lsid:zoobank.org:act:D39067BB-B013-4D67-9E01-BEA126CF5EA8